Polypoidal choroidal vasculopathy causing cystoid macular edema and the response to Ranibizumb intravitreal treatment - Amaro,Miguel Hage (2011)
PURPOSE: To report a polypoidal vascular choroidopathy clinical case causing cystoid macular edema and the response to Ranibizumab intravitreal treatment. METHODS: A 62-year old caucasian woman was referred by her comprehensive ophthalmologist for retinal avaliation. On presentation best corrected visual acuity was 20/100 in the left eye and 20/20 in right eye.Anterior segment examination was unremarkable in both eyes. Clinical examination and FA on the left eye demonstrated numerous small drusen and a cystoid macular edema due leakage from any polips in justapapilar region and from polips in the superior arcade vascular region and subretinal fluid and cystic change in the OCT.The right eye had FA normal. The patient refused to submitt a ICGV angiography. The patient was treated by intravitreal ranibizumab injections in the left eye every 4 weeks, 3 injections ,three months. RESULTS: The patient showed resolution both of cystic change and subretinal fluid in the OCT, and the visual acuity in the six months follow-up improved to 20/25. The patient was followed by 18 months at this time and the visual acuity remained stable 20/25. CONCLUSION: We reported a patient case of cystoid macular edema from a polypoidal choroidal vaculopathy that responded well to ranibizumab intravitreal injection as monotheraphy with disappearance of the initial subretinal fluid and cystic change in OCT follow-up and stop the polips.